Dekomposisi Fungsi pada Pengembangan Sistem Persediaan Barang CV. Jaya Abadi Berbasis Java - Nasrulloh Isnain (Teknik Informatika Universitas Pamulang, 2020)
CV. Jaya Abadi is a company engaged in the sale of building materials. This company in its business activities has not implemented information technology as a whole. One of the problems that need to be considered in the company's business processes is the inventory system. The inventory system is carried out using paper files which have a less effective and efficient impact and hinder company performance. Often there are errors in recording inventory. A reliable information system is needed so that the transaction process runs optimally and reduces errors made by employees. This research was conducted to solve the problem of inventory management at CV. Jaya Abadi. Based on these problems, the main objective of this study is how to improve inventory management in CV. Jaya Abadi.